2015
DOI: 10.1186/s13046-015-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic intestinal denervation modulates tumor development in the small intestine of ApcMin/+ mice

Abstract: BackgroundInnervation interacts with enteric immune responses. Chronic intestinal inflammation is associated with increased risk of colorectal cancer. We aimed to study potential extrinsic neuronal modulation of intestinal tumor development in a mouse model.MethodsExperiments were performed with male ApcMin/+ or wild type mice (4 weeks old, body weight approximately 20 g). Subgroups with subdiaphragmatic vagotomy (apcV/wtV), sympathetic denervation of the small intestine (apcS/wtS) or sham operated controls (a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Moreover, the amount of neurogenesis inversely correlates with the survival of colorectal cancer patient . Consistently in APC Min/+ mice, it has been demonstrated that vagal nerve innervation promotes tumour growth in the small intestine . Vagal neurons drive the production of protein trefoil factor 2 by splenic memory T cells helping to suppress myeloid‐derived suppressor cell (MDSC) activity.…”
Section: Endogenous Triggersmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the amount of neurogenesis inversely correlates with the survival of colorectal cancer patient . Consistently in APC Min/+ mice, it has been demonstrated that vagal nerve innervation promotes tumour growth in the small intestine . Vagal neurons drive the production of protein trefoil factor 2 by splenic memory T cells helping to suppress myeloid‐derived suppressor cell (MDSC) activity.…”
Section: Endogenous Triggersmentioning
confidence: 94%
“…They do so by driving ILC2 cells , CD4 , or dermal dendritic cells activity. However, somatosensory neurons appear to block T H 1 or T H 17 immunity as observed in the context of bacterial and fungal infection as well as anti‐tumour immunity . Neurons initiate such effects by secreting CGRP, which blocks the activity of neutrophils and CD301b + dermal dendritic cells .…”
Section: Clinical Relevancementioning
confidence: 99%
“…Like angiogenesis and lymphogenesis in cancer, the term "neo-neurogenesis" has been coined by cancer researchers to study functional roles played by the neural system in cancer 4,5 . Functional involvement of neural processes in cancer has been studied by numerous authors, such as that (1) perineural invasion has been observed in multiple cancer types 6,7 ; (2) cancer cells surrounding nerves tend to be more resistant to apoptosis 8,9 ; and (3) denervation has been found to be effective in slowing down cancer progression [10][11][12] . Furthermore, cross-talks have been observed between cancer cells and nerves, including neurites growing towards cancer cells and cancer cells invading nerves 13,14 .…”
mentioning
confidence: 99%
“…The role of the gut-brain axis, which includes the ENS, in carcinogenesis is underestimated and vastly understudied. For example, colon tumor development in the Apc(Min/+) mouse model is inhibited after vagotomy, but not by sympathetic denervation (Liu et al, 2015). Last but not least, the ENS is the target of paraneoplastic neurological autoimmunity often associated with small cell lung cancer.…”
Section: Transmittermentioning
confidence: 99%